Mahasiswa dan Tantangan Diseminasi Moderasi Beragama di Era Disrupsi Digital - Rifdi, Moh. (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Religious moderation is the perspective or perspective of religious believers so that they do not go to extremes and respect each other's religious differences in order to achieve peace in society in general. The existence of religious moderation in the era of digital disruption, which is almost all informal, is very threatened and becomes a challenge in itself because the spread of radicalism uses a lot of digital media. From this background, there is a need for real action, especially for students in disseminating religious moderation with preventive, promotive, and curative movements (P2K) in order to minimize radical ideas. The purpose of this paper is to provide strategies in disseminating religious moderation in the digital era, so that religious moderation is always a framing to maintain the attitude of not blaming each other and respecting each other's religious differences in a multicultural life. The research method in this paper is qualitative, using a library research approach, and the data is obtained from the literature studies that have been processed. The existence of preventive, promotive, and curative (P2K) movements spearheaded by students as active and dynamic youth indicates the importance of maintaining and always disseminating religious moderation in the era of digital disruption. Therefore, with this concept, it is hoped that it can be a solution in disseminating religious moderation in the era of digital disruption to various media corners so that the peace of the general public is always maintained.